Linear algebra tests: Jacobi symmetric matrices with equal diagonal elements - Arushanian, O.B. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2000)
The formulas for computing determinants, eigenvalues, and eigenvectors as well as for inverting Jacobi symmetric matrices with equal diagonal elements are given. As an illustration, one class of such matrices arising frequently in practical computations is considered.